Leadership passages : - Dotlich, David L. (John Wiley & Sons, Inc., 2004)
Leaders face numerous critical crossroads in their careers, moments that can provide extraordinary learning and growth opportunities or ensnare them and prevent further development. The good thing about these passages is that they're predictable, and with proper preparation, leaders not only can survive them to become stronger but can use these experiences to enhance their leadership, compassion, and effectiveness.